Continuing professional development proposed guidelines of national medical commission, India – A critique - Guru S. Gowda; Mahesh Gowda; Nadukuru N. Raju; Suresh Bada Math (Indian Journal of Psychiatry)
The National Medical Commission ‘Ethics and Medical Registration Board’ (EMRB) proposed ‘The registered Medical Practioner (Professional Conduct) Regulations’ 2022 on 23.05.2022 for public opinion. One of the major regulations included Continuing Professional Development (CPD) Guidelines in Chapter 2, Section 5. The main objective of the CPD Guidelines is to upgrade knowledge and skills regularly and ensure compliance with existing guidelines by the Registered Medical Practitioner (RMP) under NMC. The drafted CPD guidelines provide a framework for uniform, clear, and structured CPD modules for both in-person conferences and online webinars as well as accreditation. The proposed CPD guideline will ensure adequate up-gradation of knowledge, along with the improved quality of the content of CPD. This article aims to map the trajectory of CPD on its roads from origin to becoming a reality in the Indian scenario as well as identify the challenges and opportunities in implementing CPD in India.